Micro/Nanofiber with Hollow Silica Nanoparticles Thin-Film for Airborne Molecular Contaminants Real-Time Sensing - Longfei Niu; Guorui Zhou; Xinxiang Miao; Xiaodong Yuan; Rahul Kumar; Hao Liu; Yilan Jiang; Xinshu Zou; Hai Zhou; Haibing Lü (Advances in Condensed Matter Physics)
A novel chemical sensing approach detecting airborne molecular contaminants (AMCs) or compounds is demonstrated by using single-mode optical microfibre (OMF) coated with hollow silica nanoparticles (HSNs). The concentration of AMCs, which were volatilized on the surface of the tapered microfibre coated with HSNs, influences the transmission loss of the microfibre. Tapered OMF was fabricated using a high-precision electrically controlled setup, and coatings of HSNs were prepared by meniscus coating method. The transmission loss of three OMFs with different diameters and the same thick coating were tested to determine the relationship between AMC concentrations and transmission loss of coated OMFs. Experimental results showed that the transmission loss increases with increasing concentration of AMCs. The sensitivity for volatile simethicone was 0.0263 dB/mg/m3 obtained by the coated OMF with diameter of 2.5 μm, and the sensitivity values of coated OMF with diameters of 5 μm and 6 μm were 0.0024 and 0.0018 dB/mg/m3, respectively. Thus the proposed coated OMF can be used in enclosed space for AMCs sensing.